The effect of surgery in patients of brain injury with pneumonia complications on the recovery rate at the central referral hospital in eastern Indonesia: non-experimental study - RiznaAudina; Hafid Bajamal, Abdul; Dwi Wahyu Widodo, Agung (International Journal of Psychosocial Rehabilitation, 2020)
Background: A traumatic brain injury is caused by a sudden collision from the outside of the brain and eventually causes brain dysfunction. One complication in brain injury is found in 5-13% of patients with traumatic brain injury.Aim: This study aimed to investigate the outcomes for patients by observing the profile of brain injury patients who have pneumonia in a central referral hospital in eastern Indonesia Method: This study was conducted with a descriptive approach. This study observed personal data, causes of brain injury, diagnosis, treatment, and outcome of the patients after receiving treatment. The samples were 27 patients and used purposive sampling technique. Results: The results showed 27 patients (24 males and 3 females) with age ranges from 41 years to 60 years (48.15%). The most common cause of traumatic brain injury found was a traffic accident (81.48%). Most diagnoses referred to Glasgow Coma Scale were a severe brain injury (70.07%) and the Surgical treatment that performed were craniotomy (40.74%) and decompression (40.74%). Tracheostomy was performed in 10 patients (37.04%). The most common cause of pneumonia is hospital-acquired pneumonia (88.89%), with bacterial culture results being Pseudomonas aeruginosa (40.74%). Patients mostly stayed at the hospital for between 11 and 30 days (70.37%), and 70.37% of them died. Conclusion: Patients with severe brain injury caused by traffic accidents who had pneumonia did not show a positive result. Giving surgical procedures, tracheostomy, hospitalization, and treatment were not able to reduce the mortality percentage of the patients due to severe brain injury with pneumonia complications.